Between-group competition, intra-group cooperation and relative performance - Cárdenas, Juan C.; Mantilla, César (Frontiers in Behavioral Neuroscience, 2015)
We report the results of a new public goods experiment with an intra-group cooperation dilemma and inter-group competition. In our design subjects receive information about their relative individual and group performance after each round with non-incentivized and then incentivized group competition. We found that, on average, individuals with low relative performance reduce their contributions to the public good, but groups with low performance increase theirs. With incentivized competition, where the relative ranking of the group increases individual payoffs, the reaction to relative performance is larger with individuals contributing more to the group; further, we observe that the variance of strategies decreases as individual and group rankings increase. These results offer new insights on how social comparison shapes similar reactions in games with different incentives for group performance and how competition and cooperation can influence each other.